The impact of disease activity on the quality of life, mental health status, and family dysfunction in Colombian patients with rheumatoid arthritis (2003)
This study investigated the relationship between activity of disease, mental health status, quality of life, and family dysfunction in northwestern Colombian patients with rheumatoid arthritis (RA). Seventy-nine patients completed a 2-phase study that included physical examination (objective measurement of disease activity according to adapted American College of Rheumatology criteria) and a pretested questionnaire that sought information on helplessness, disability, depression, anxiety, quality of life, arthritis self-efficacy for pain, and other symptoms, as well as family dysfunction and socioeconomic status.Nineteen patients (24%) had active RA, 48 (61%) had moderately active RA, and 12 (15%) were in remission. Symptoms of depression, helplessness, disability, pain, anxiety, lower quality of life, and self-efficacy were associated with RA activity regardless of age, sex, and duration of the disease. Symptoms of depression were directly correlated with anxiety, helplessness, pain, and disability and inversely correlated with quality of life and self-efficacy.Although family dysfunction was present in 39% of patients, no associations between family dysfunction, activity of RA, mental health variables, socioeconomical status or quality of life were observed. These results indicate that RA activity significantly influences mental health status and quality of life in this population. Accordingly, a holistic conception of therapy should guide the treatment of patients with RA.